Online marketing - Pavlova, Adelina (Jihočeská univerzita, 2017)
This thesis was focused on creating an advertising campaign for a company "Desired House", which produces wood. The company "Desired House" is one of the largest companies in the Altai woodworking industry engaged in harvesting and processing wood. Since 2009, one of the company's strategic directions has been the development of the wooden house building industry in the region. To this end, within the framework of the company, a project aimed at creating a complex of house-building production and production facilities with in-depth processing of wood was developed and implemented to produce a series of spacious, eco-friendly, affordable wooden houses and all the necessary components for them. However, their marketing activities did not allow it to prosper in its full scope. In theoretical part I observe the development of marketing concept as a whole and theoretical basis of online marketing in particular. The information was primarily derived from the books and online resources. The important part was the researching part of online advertising and its measurement. In the practical part, primary source of data is internal to the company observed. The tools of Yandex.Metric was used to measure and plan advertising activities. SWOT analysis was performed to assess company's abilities and areas in order to develop. In the last part, an advertising campaign was carried out based on recommendations. The website was renovated.
Online marketing
Keywords: online marketing; online advertising; promotion; website; online marketing; online advertising; promotion; website